A Systematic Review of Pliance, Tracking, and Augmenting. (September 2017) - Kissi, Ama; Hughes, Sean; Mertens, Gaëtan; Barnes-Holmes, Dermot; De Houwer, Jan; Crombez, Geert
Within relational frame theory, a distinction has been made between three types of rule-governed behavior known as pliance, tracking, and augmenting. This review examined whether there is support for the concepts of pliance, tracking, and augmenting in the experimental analysis of behavior; whether these concepts refer to distinct functional classes of behavior; and how these concepts have been operationalized in experimental (behavioral-analytic) research. Given that the concepts of pliance, tracking, and augmenting were first defined by Zettle and Hayes, we confined our review to studies published in or after 1982. Our results indicate that (a) experimental research investigating pliance, tracking, and/or augmenting is extremely limited; (b) it is difficult to determine the extent to which the concepts of pliance, tracking, and augmenting allow for relatively precise experimental analyses of distinct functional classes of behavior; and (c) pliance and tracking have been operationalized by using a limited set of procedures.